Implementasi Pembinaan Konsepsi Model Pembelajaran Up Grading untuk Meningkatkan Kualitas Mengajar Guru di Sekolah Dasar Binaan Segugus 05 Kopang Lombok Tengah - Ahmad, Ahmad (UNDIKMA, 2021)
The purpose of this research is to improve the teaching quality of teachers through the Up Grading learning model, especially in elementary schools assisted by the 05 Kopang cluster. This research method used action research with a qualitative approach. Data collection techniques using observation techniques (observation), field notes, and documentation. The data analysis technique in this study used qualitative data analysis techniques. The results showed that the implementation of the Up Grading learning model conception development was able to improve the quality of teacher teaching. The results of this study indicate that Up Grading Learning has a positive impact on improving teacher performance. This can be seen from the more stable students' understanding of the material presented by the teacher (learning mastery increases from cycles I, II, and III) which are 65.00%, 75.00%, and 85.00%, respectively. In cycle III, classical student learning completeness has been achieved. This research was successful because there was an increase with the research success criteria of 10% per cycle.